2014
DOI: 10.1017/s0144686x14000142
|View full text |Cite
|
Sign up to set email alerts
|

How similar, how different? On Dutch media depictions of older and younger people

Abstract: By providing information on society at large, the media help to establish and maintain relations between various social groups, such as between younger and older people. They may also disturb the formation or maintenance of such relations,e.g.by stimulating the ‘othering’ of the out-group members. The aim of the present study was to trace how the different strategies of ‘othering’ are applied by Dutch news media in their portrayal of older and younger citizens. The analysis showed that the most notable discrep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 36 publications
2
23
0
1
Order By: Relevance
“…In newspaper coverage, young people are portrayed as an inherently different social group, who are to be kept out of public spaces. Although, in line with Lepianka (2015b), we expected that this portrayal is key to 'othering' youngsters, it is unexpected that this othering includes an image of illegitimate youth climate activism and a structural underestimation of young activists' abilities and capabilities of knowing and exerting their climate interests. Media propensity to criminalize youth remains obvious.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In newspaper coverage, young people are portrayed as an inherently different social group, who are to be kept out of public spaces. Although, in line with Lepianka (2015b), we expected that this portrayal is key to 'othering' youngsters, it is unexpected that this othering includes an image of illegitimate youth climate activism and a structural underestimation of young activists' abilities and capabilities of knowing and exerting their climate interests. Media propensity to criminalize youth remains obvious.…”
Section: Discussionmentioning
confidence: 81%
“…Westman's argument has been widely confirmed, in research on the marginalization and exclusion of young people from public spaces (Moris and Loopmans 2019) and the criminalization of youth (Lepianka 2015a(Lepianka , 2015bLevinsen and Wien 2011;Welch et al 2002). Gendron et al (2016) point at the complexity of ageist language, which includes unintended as well as well-intentioned ageist remarks, ranging from contempt, derogatory expressions to positive images of youth.…”
Section: Ageist Domination Of Youthmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, we found amongst residents a limited sense of group belonging, and, even more, clear instances of 'othering', i.e. practices of setting a group of people apart as different (Lepianka, 2015(Lepianka, , pp. 1098(Lepianka, -1099Mountz, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest, therefore, that ageing is not solely an inevitable natural and biological process. Studies indicate that there is a dualistic understanding of ageing and older people in society at present and that older people are often rated high on traits associated with warmth (generous, helpful or kind) and low on competence (forgetful, conservative, narrow-minded or dependent) (Lepianka, 2015). Furthermore, Hummert et al (2004) found that older and younger adults have stereotypes of both older and younger people.…”
Section: Stereotypes Of Older People and Lonelinessmentioning
confidence: 99%